2008
DOI: 10.1177/1753193408094706
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Clinical Study Comparing Palmar and Dorsal Fixed-Angle Plates for the Internal Fixation of AO C-Type Fractures of the Distal Radius in the Elderly

Abstract: Current surgical treatments for distal radial fractures include dorsal and palmar plate fixation. We report results of a randomised study comparing these methods for AO C1-3 fractures. The emphasis was placed on the early postoperative functional recovery within the first 6 months as this interval is of decisive importance for elderly patients. Thirty patients with unilateral AO C1-3 fractures were enroled, 15 were treated with a palmar plate and 15 received a dorsal Pi-plate. Results were assessed 6 weeks, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 25 publications
3
36
0
2
Order By: Relevance
“…[3][4][5]18 However, the direct dorsal approach should not be totally excluded because it indeed provides surgeons with a good opportunity to directly restore the disrupted dorsal cortical rim and realign the rotated dorsal cortical fragments that cannot be reduced indirectly. 14,15 Because of the low-profile design and multiple available shapes of this dorsal-plating system, the 2.4-mm titanium dorsal locking plate can be easily applied without apparent tendon irritation; furthermore, a column-specialized fixation can be achieved by using a dorsal locking plate on the medial column and a dorsoradial plate or styloid plate on the radial column. 19,20 The dorsal and volar plates are mainly used in cases of dorsal rim comminution and metaphyseal comminution, respectively; thus, the 2 groups in this study were not identical and are therefore not entirely comparable.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]18 However, the direct dorsal approach should not be totally excluded because it indeed provides surgeons with a good opportunity to directly restore the disrupted dorsal cortical rim and realign the rotated dorsal cortical fragments that cannot be reduced indirectly. 14,15 Because of the low-profile design and multiple available shapes of this dorsal-plating system, the 2.4-mm titanium dorsal locking plate can be easily applied without apparent tendon irritation; furthermore, a column-specialized fixation can be achieved by using a dorsal locking plate on the medial column and a dorsoradial plate or styloid plate on the radial column. 19,20 The dorsal and volar plates are mainly used in cases of dorsal rim comminution and metaphyseal comminution, respectively; thus, the 2 groups in this study were not identical and are therefore not entirely comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a close relation between the extensor tendons and dorsally placed implant. In current literature, published complications rates in dorsal radius plating are as high as 60 % (19,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…6 The angle-stable screws gave more secure fixation, even in severely osteoporotic bone, 7,8 and the volar position of the plate proved to give rise to fewer complications from impingement by tendons. 5,9 The risk of complications after volar plating in terms of tendon rupture, hardware problems and nerve compression is reported to be approximately 10%, 10 and between 15% and 34% of patients have their hardware removed within a year. [11][12] Published studies that compare the clinical outcomes of volar plating and external fixation have shown that those treated with a volar plate return to normal function more quickly but the long-term outcome is equal after both treatments.…”
mentioning
confidence: 99%